Restrukturisasi Independensi Hakim dalam Sistem Peradilan Pidana yang Berwawasan Pancasila - Muhammad Ramzi Maulana; Pujiyono Pujiyono (Universitas Batanghari Jambi, 2021)
The position of judicial power is outside the executive and legislative powers. This placement can be intended so that the judge does not use his power to oppress people arbitrarily and does not make legal rules that can injure the community. Currently, judges are under judicial power which is neutral and free from the influence of other powers and has an independent attitude in hearing without intervention from the executive and legislative powers. The purpose of this research is to find out the reality of the independence of judges in giving decisions and judging people who are in dispute and see how the influence of Pancasila values on judges in giving decisions based on the values contained in Pancasila, so that they can provide justice based on the laws that live in society. . The method in this study uses a normative approach, which is the reference source of this study using the literature approach, conceptual approach and value approach. The results of the research show that currently the position of judges independently is still limited, considering that in deciding criminal dispute cases using penal means, judges do not decide based on the values contained in Pancasila. This is proven by the limitations of judges in deciding a case, where individually a judge cannot give a decision according to his / her conscience and is even constrained by the written rules of the law. This shows as if the judge's personal freedom is bound by the demands and charges given by the public prosecutor. Departing from this condition, it is necessary to rearrange the independence of the judiciary in adjudicating and deciding disputes which must be based on the Pancasila insight. This is intended so that the judiciary becomes an independent institution based on the Pancasila legal culture that is more religious, humanitarian, and justice based on the values that live in society.